2008
DOI: 10.1253/circj.72.179
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glomerular Filtration Rate With Unsuccessful Primary Percutaneous Coronary Intervention and Subsequent Mortality in Patients With Acute Myocardial Infarction From the HIJAMI Registry

Abstract: umerous randomized trials have successfully demonstrated the beneficial effects of early percutaneous coronary intervention (PCI) for patients with acute myocardial infarction (AMI). [1][2][3] However, most patients with complications of renal insufficiency were excluded from randomized trials; therefore, the clinical effects of PCI for these patients have not been determined.In the past decade, patients with end-stage renal disease were associated with a decreased procedural success rate. [4][5][6] The develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…[23][24][25] This work confirms those findings in unselected patients, despite considerable advances of modern pharmaceutical treatment in acute MI. We show that, as well as thrombolytic agent, medications with risk benefit after MI, are used less frequently during the index hospitalization and follow-up periods with declining renal function.…”
Section: Renal Function and Use Of Medical Therapysupporting
confidence: 86%
See 1 more Smart Citation
“…[23][24][25] This work confirms those findings in unselected patients, despite considerable advances of modern pharmaceutical treatment in acute MI. We show that, as well as thrombolytic agent, medications with risk benefit after MI, are used less frequently during the index hospitalization and follow-up periods with declining renal function.…”
Section: Renal Function and Use Of Medical Therapysupporting
confidence: 86%
“…17,22,23 As a medical treatment, this is partly associated with advanced age, increased comorbidity and more compromised hemodynamic status in decreased renal function. 26 Wright et al described that patients with any degree of renal dysfunction are more likely to have contraindications to thrombolytic therapy than those without renal dysfunction.…”
Section: Renal Function and The Use Of Reperfusion Strategymentioning
confidence: 99%
“…CRS, which is now widely accepted to be a distinct clinical entity 2, 3) affecting patients with cardiovascular disease in different clinical settings [2][3][4][5][6][7] , is particularly associated with a poor prognosis in individuals with acute coronary syndrome [4][5][6][7][8] . Numerous epidemiologic and clinical observational studies have revealed a substantially increased risk of cardiovascular events in patients with chronic kidney disease (CKD) 2-6, 9, 10) , and observational studies have identified cardiovascular disease as the leading cause of death among patients with renal failure, especially those on dialysis [11][12][13][14] .…”
Section: Blood Sampling For Biochemistry Blood Cell Count Study and mentioning
confidence: 99%
“…The risks of CKD included not only the progression to end-stage renal failure but also the occurrence of adverse cardiovascular outcomes. [5][6][7][8][9] Previous studies have demonstrated that CKD is an independent risk factor for morbidity and mortality in the general population, 10 as well as in patients with cardiovascular diseases such as post acute myocardial infarction (AMI). 11 Anavekar et al 11 reported that CKD was a common and significant independent risk factor for cardiovascular events in AMI patients based on data from the Valsartan in Acute Myocardial Infarction Trial (VALIANT).…”
Section: Introductionmentioning
confidence: 99%